Chitosan and its derivatives-based nanostructures in conjunction with their versatile applications in bio-medicine for alleviating contiguous diseases - Anwar, Ayesha; Imran, Muhammad; Warsi, Muhammad Farooq; Alsafari, Ibrahim A.; Parra-Saldívar, Roberto; Gutiérrez-Soto, Guadalupe; Iqbal, Hafiz M. N. (Frontiers in Materials, 2025)
Due to its unique properties and inherent biocompatibility, chitosan (CH), a multifunctional biopolymer derived from chitin, has garnered significant interest in deployment in various scientific domains. The Food and Drug Administration (FDA) authorized CH to employ an injury remedy and a nutritional supplement. Furthermore, CH has facilitated advancements in numerous biological applications, particularly nano-carriers and scaffolds for tissue engineering. It is an ideal choice for wound care because of its hemostatic, antioxidant, and antimicrobial properties. The hydrophilic nature of CH makes it a perfect precursor. This review focuses on the advent of chitosan-based nanostructures, highlighting their physicochemical characteristics, methods for structural modification, and the functionalization of chitosan into its derivatives, which may aid in understanding its benefits and cellular significance. It has been demonstrated that CH nanostructures offer remarkable encapsulation efficiency and extended-release patterns in drug delivery, resulting in higher therapeutic efficacy and fewer side effects. Furthermore, due to their mucoadhesive properties, they are particularly well-suited for transdermal drug delivery. Nanostructures based on CH exhibited optimum activity in biosensing and diagnostic imaging. The potential of CH to interact with targeting ligands enhances the early detection of disease and integration of CH in focused imaging modalities. Moreover, CH variable surface chemistry facilitates attachment to biological entities, resulting in improved diagnostic accuracy, rendering the insertion of bioactive substances possible. Furthermore, the degradable nature of CH offers a minimal long-term impact, alleviating challenges related to ecological sustainability. As long as CH-modified nanostructures have become prevalent in healthcare fields and researchers strive to explore novel and more effective uses, medical care will advance, and a range of health problems will be resolved. This review provides a comprehensive overview of the current status of CH-based nanostructures in the bio-medical field, highlighting their potential to revolutionize therapeutic and diagnostic methodologies. In conclusion, several perspectives on its potential are presented, including new approaches to alterations, directed modification through the association between framework and operation, and the path towards growth for activities and implementations.